2022
DOI: 10.1111/jbi.14480
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of genetic diversity and species richness of North American amphibians

Abstract: Aim: Ecological limits on population sizes and the number of species a region can sustain are thought to simultaneously produce spatial patterns in population genetic diversity and species richness due to the effects of random drift operating in parallel across population and community levels. Here, we test the extent to which resource-based environmental limits jointly determine these patterns of biodiversity in amphibians.Location: North America.Taxon: Amphibians. Methods:We repurposed open, raw microsatelli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…From a geographic perspective, protecting areas that contain high intraspecific genetic diversity, not just high species richness (e.g., ref. 117 ), must become an important component in evaluating biodiversity hotspots ( 118 , 119 ). Genomic taxonomy now provides the means to acknowledge more biodiversity without more species, so researchers and conservationists are better armed to unveil those species’ secrets and plan their survival.…”
Section: General Recommendationsmentioning
confidence: 99%
“…From a geographic perspective, protecting areas that contain high intraspecific genetic diversity, not just high species richness (e.g., ref. 117 ), must become an important component in evaluating biodiversity hotspots ( 118 , 119 ). Genomic taxonomy now provides the means to acknowledge more biodiversity without more species, so researchers and conservationists are better armed to unveil those species’ secrets and plan their survival.…”
Section: General Recommendationsmentioning
confidence: 99%
“…In the same region, Schmidt et al. (2022) analysed microsatellite data from 19 amphibian species; they found that genetic diversity was not predicted by the environmental variables they used and that areas with high species richness also had high genetic structure, but low genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Nearctic amphibian species, the most important predictors of genetic diversity were taxonomic family, number of sequences, and for salamander species (N = 98), those at more northern latitudes had lower genetic diversity (Barrow et al, 2021). In the same region, Schmidt et al (2022) analysed microsatellite data from 19 amphibian species; they found that genetic diversity was not predicted by the environmental variables they used and that areas with high species richness also had high genetic structure, but low genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Nearctic amphibian species, the most important predictors of genetic diversity were taxonomic family, number of sequences, and for salamander species (N = 98), those at more northern latitudes had lower genetic diversity (Barrow et al, 2021). In the same region, Schmidt et al (2022) analyzed microsatellite data from 19 amphibian species; they found that genetic diversity was not predicted by the environmental variables they used and that areas with high species richness also had high genetic structure, but low genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Nearctic amphibian species, the most important predictors of GD were taxonomic family, number of sequences, and for salamander species (N = 98), those at more northern latitudes had lower GD (Barrow et al, 2021). In the same region, Schmidt et al (2022) analyzed microsatellite data from 19 amphibian species; they found that GD was not predicted by the environmental variables they used and that areas with high species richness also had high GS, but low GD. Amphibians are the most threatened group of vertebrates on the planet (Harfoot et al, 2021), and are also particularly vulnerable to habitat loss, pollution, climate change, and disease.…”
Section: Introductionmentioning
confidence: 99%